PERKEMBANGAN SISTEM PERAWATAN MESIN DI INDUSTRI PROSES - Sally Cahyati; Bambang Pramudya (PERTETA, 2007)
ABSTRACT For most companies, maintenance represents a very significant function within the overall production environment. The developments in automation, and the resulting complexity of the systems involved, have made the reliability of the machines even more important. This is especially true in the process industry, characterized by expensive specialized equipment and strict environmental considerations. Competition and the drive for profits are forcing companies to implement various productivity improvement efforts. Maintenance function, although is to serve to production, has a fundamental role since it has a direct effect over competition through its impact in productivity (global costs reduction).Diterima: 23 Agustus 2006; Disetujui: 20 Maret 2007